(untitled) (Revista de Ciências Agroveterinárias, 2018)
The study aimed to evaluate the effect of zinc concentration applied to the seed treatment on the physiological quality of bean seeds and leaf content of the micronutrients iron, copper, zinc and manganese of BRS Expedito. The experiment was carried out with common bean seeds obtained from 2014/2015 growing season. The treatments using the following concentrations of zinc were applied via seed treatment with concentrations of 0, 12, 24, 36 and 48 g Zn 100 kg-1 of seed. Emergence assessments of emergence speed index, cold test, length of shoot and roots, dry weight of shoots and roots of seedlings and each micro-nutrient contents: Fe, Cu, Zn and Mn were conducted. The results of the variables emergence, emergence speed index and cold test showed no significant effects of increased Zn concentrations in seed treatment. However, in the analysis of seedling growth, Zn promoted an increase in hair and root length and dry matter produced by both shoot and root. The Zn content in leaf tissue increased manganese according to the increase of the Zn concentration in seed treatment. Seed treatment with Zn promotes increased growth and leaf content of this element to BRS Expedito.